2021
DOI: 10.1097/iae.0000000000003351
|View full text |Cite
|
Sign up to set email alerts
|

CHARACTERISTICS AND MANAGEMENT OF MYOPIC TRACTION MACULOPATHY IN MYOPIC EYES WITH AXIAL LENGTH LESS THAN 26.5 mm

Abstract: Purpose:To explore the characteristics and underlying mechanisms of myopic traction maculopathy (MTM) with axial length less than 26.5 mm and to assess the effectiveness of macular buckling for the treatment of MTM.Methods:Thirty-eight MTM eyes with axial length less than 26.5 mm were prospectively enrolled. Thirty-one eyes received surgery, and they were followed up for at least 6 months. Characteristics of MTM and surgical outcomes were evaluated.Results:Of the MTM eyes, 92.11% (35/38) showed posterior staph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Compared with previous studies that showed that an increase in AL is associated with a higher likelihood of RD, our findings indicate that a shorter preoperative AL reduces the risk of RD. [14][15][16] This aligns with the established link between longer eyes and increased risk of detachment. 17 While several reports have identified longer AL as a risk factor for detachment in children after surgery, most have only briefly touched upon this subject.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Compared with previous studies that showed that an increase in AL is associated with a higher likelihood of RD, our findings indicate that a shorter preoperative AL reduces the risk of RD. [14][15][16] This aligns with the established link between longer eyes and increased risk of detachment. 17 While several reports have identified longer AL as a risk factor for detachment in children after surgery, most have only briefly touched upon this subject.…”
Section: Discussionsupporting
confidence: 75%
“…The findings of Mimura et al and Chen et al provide evidence for this claim. 14,17 It is possible that the shorter AL (≤ 23.4 mm in our patient group helped to protect against increased vitreoretinal traction), which may have contributed to the development of retinal tears or detachment after pediatric cataract surgery. This protective mechanism warrants further investigation given its potential clinical implications.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, our previous study presented favorable outcomes of MTM eyes after receive MB surgery, some of which had VIFs. 26 Dome-shaped macula is recognized as a protective factor for the occurrence of MTM. 27 One of the morphological results of MB surgery is the formation of an iatrogenic dome-shaped macula, leading to an effective mitigation of MTM and preventing its deterioration.…”
Section: Discussionmentioning
confidence: 99%
“…Parolini et al [41] retrospectively reviewed 157 MTM eyes after MB or PPV or combined surgery, and concluded that PPV is better in addressing the tangential traction existing on the vitreo-retinal surface, while MB is better in resolving the perpendicular traction induced by posterior staphyloma. As the PPV and MB focus on two different aspects of the MTM pathology, surgeons should select proper approaches according to the MTM stages and classifications, separately or combined [50][51][52] .…”
Section: Analysis Of Authors and Co-cited Authorsmentioning
confidence: 99%